Linear and Angular Displacement Relationship of Natural Rubber Engine Isolator - Putra, Azma; ABDULLAH, Mohd Azman; Salim, Mohd Azli (Trans Tech Publications, 2014)
Linear and angular displacement is an important criteria for incompressible materials. Natural rubber is a one of the incompressible material because it has a potential to make uniform displacement when apply the quantum of force. This paper represents the linear and angular displacement of natural rubber engine isolator, respectively. The identity formulation is developed and trivial solution is faced. To doing so, the identity formulation is derived and finally the equation of relationship between linear and angular displacement is derived. Finally, the result has shown the transformation of these two displacements with quantum of frequency.